Architecture and distribution of human corneal nerves. Issue 6 (4th November 2009) - Al-Aqaba, Mouhamed A; Fares, Usama; Suleman, Hanif; Lowe, James; Dua, Harminder S
Abstract : Aims: To comprehensively study the gross anatomy of human corneal innervation. Methods: Twenty-one specimens, including 12 normal human corneas from seven deceased patients, two eye-bank corneo-scleral buttons, two eye-bank corneo-scleral rims and five post-surgical specimens from three patients with keratoconus were studied. Corneal whole mounts were stained for cholinesterase enzyme using the Karnovsky & Roots direct colouring thiocholine modification of acetylcholinesterase (AchE) technique. Results: Approximately 44 thick nerve bundles were found to enter the human cornea in a relatively equal distribution round the limbus and move randomly towards the central cornea. At the mid-peripheral zone, anterior stromal nerves showed a characteristic budding and branching pattern. After passing through Bowman's zone they were noted to terminate into bulb-like thickenings from which multiple sub-basal nerves arose. The perforation sites were predominantly located in the mid-peripheral cornea. The orientation of sub-basal nerves was mainly vertical at their origin from the perforation sites. Nerves from all directions converged towards the infero-central cornea to form a characteristic clockwise whorl pattern. Conclusions: This study provides a comprehensive account of the architecture and distribution of nerves in the human cornea. It reconciles some of the existing information obtained from other modalities of investigation and identifies some novel features that provide a more complete picture of corneal innervation.